Exploring the Use of Court-Connected Alternative Dispute Resolution Mechanisms in Intimate Partner Disputes in Ghana: A Case Study of Greater Accra - Saa, V. Y. (University of Ghana, 2025)
In Ghana, the resolution of disputes between intimate partners such as divorce, child custody, and property division has traditionally been handled through formal litigation or community-based interventions steeped in cultural norms. However, these methods often leave parties feeling disempowered and unheard, especially within a rigid legal system that may not accommodate the emotional complexities of intimate relationships. For the first time, this study takes a groundbreaking approach by using a qualitative methodology, through the lens of legal consciousness theory to explore how Court-Connected Alternative Dispute Resolution (CCADR) is being employed to resolve intimate partner disputes in Ghana. Through the voices of 28 disputants, and live observation of 14 couple mediation sessions at two CCADR units in Greater Accra, this research delves into the lived experiences of those navigating these processes, offering new insights into the challenges and opportunities that arise. The findings reveal the transformative potential of CCADR offering a more humane, culturally sensitive, flexible and emotionally supportive avenue for conflict resolution. Participants reported a higher sense of control over the resolution process, reduced financial strain, and the opportunity for constructive dialogue. However, challenges remain, including power imbalances between disputing parties, inconsistent enforcement of mediation outcomes, limited legal recourse in cases of non-compliance, and the complexity of navigating CCADR without professional legal guidance. This study contributes to knowledge by providing insights into the practical application of CCADR in resolving intimate partner disputes in a Ghanaian context, positioning it as a tool for addressing deeply personal conflicts in ways that are more culturally attuned and emotionally supportive. The study recommends that the Judicial Service of Ghana considers offering CCADR options at the Court Registry stage to allow clients to opt for that option early in the litigation process.
PhD. Sociology
Keywords: Alternative Dispute Resolution; Court; Intimate; Partner Disputes; Ghana